The Implication of Using Social Media During the Pandemic on Indonesia Netizens’ English Skills - Ratna Purnamasari; Totoh Tauhidin Abas (English Language Education Department, Universitas Majalengka, 2022)
The COVID-19 pandemic has led to a rapid increase in the use of social media. With the increasing use of the internet, it is becoming easier to access information in multiple languages, especially English. This study wanted to see that the increasing frequency of playing social media was proportional to its usefulness in helping participants improve their English skills. This study aims to describe how important social media is to help participants' English language skills. This study uses a qualitative descriptive approach to describe a phenomenon related to the problem. The participants were 20 people as a random sample who were social media users from a population called netizens. The results of the study reveal that the use of social media as a tool to develop English skills is known to have little effect on active skills which are writing and speaking, but has a small impact on passive skills which are reading and listening.